Comparison of colour improvement and stability of white spot lesions following infiltration, micro-abrasion, or CPP-ACP treatments in vitro - Phan, Anh Chi; Le, Thi Nhat Linh; Dang, Khac An (Tạp chí Y Dược Huế, 2022)
Objective: The objective was to compare the colour improvement of white spot lesion and the colour stability of treated enamel to after discolouration in vitro. Method: Artificial WSLs (2*2 mm) were created on the outer surface of 60 permanent premolars and randomly allocated to 4 groups. Specimens were treated with infiltration (RI), CPP-ACP (CPP), and micro-abrasion (MA) or remained untreated (UT).Groups were discoloured for 24 hours in tea or tea + citric acidVisible colour changes (ΔE) were measured spectrophotometrically on following time points: immediately after lesion formation, immediately after treatment, after 30 days of immersion in artificial saliva, anh aftere discolouration. Data were analyzed using SPSS 20 software. Results: WSL formation increased in all groups. ΔE1 is creater 3.7 in all groups but only infiltration reduced this effect to baseline. Highest ΔE4was obtained by CPP-ACP and resin infiltration is lowest. Between the RI and MA treatment groups, ΔE4 did not differ significantly. The improvement was more stable for infiltration and micro abrasion during discolouratio compare to the others (ΔE4 < 3.7). Conclusions: The method of infiltration improves the aesthetics of white spot lesions immediately after treatment and maintains treatment results during the follow-up period. Micro abrasion improved white spot aesthetics during the follow-up period. These two methods WSLs were stable following discolouration challenge.